(untitled) (Al-Academy, 2025)
Design is the key to many promotion and marketing problems at the present time, and it is the source of ideas that present design solutions as communicative messages. Therefore, design is a priority in knowledge, understanding and know-how, as it provides these advertising topics with more content and connotations to produce meanings that are characterized as persuasive and directive on a level. Commercial exchange and the provision of goods, and this is what necessitated the existence of working mechanisms and functions for both concepts, design and promotion, as they are two trends that differ in their ways and meet in one goal. This matter is important in presenting advertising topics that take a commercial approach to touch the needs of individuals, society, organizations and production companies, which necessitated identifying the most important Those design ideas and methods that achieve success by adopting the principle of promotion.